2000
DOI: 10.1007/pl00008529
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Loma salmonae (Microsporidia) under laboratory conditions

Abstract: The viability of the fish-infecting microsporidian Loma salmonae Morrison and Sprague, 1981 was determined under laboratory conditions by polar filament extrusion and infectivity to chinook salmon (Oncorhynchus tshawytscha). Extrusion rates of isolated spores decreased from 51.0% to 0.0% by 100 days after storage in fresh or sea water at 4 degrees C. Spores stored up to 95 days in either solution infected 80.0-100.0% of exposed chinook, although no spores infected fish at 100 days in one trial. Viability in Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Two seawater transmission modes are likely, given the path of transmission through the gut (Shaw et al 1998): inter-and intraspecific piscivory among young salmon (or feeding on tissues from dead fish) in coastal near-shore habitats prior to seaward migrations and seawater transmission by ingestion of free spores (Kent et al 1989(Kent et al , 1995. The latter mode is supported by evidence suggesting spores can be viable in seawater for up to a year (Shaw et al 2000b). Another, possibility is that the low overall genetic variation in L. salmonae could be the result of recent translocation of this parasite.…”
Section: Brown Et Al: Genetic Variation In Loma Salmonaesupporting
confidence: 56%
“…Two seawater transmission modes are likely, given the path of transmission through the gut (Shaw et al 1998): inter-and intraspecific piscivory among young salmon (or feeding on tissues from dead fish) in coastal near-shore habitats prior to seaward migrations and seawater transmission by ingestion of free spores (Kent et al 1989(Kent et al , 1995. The latter mode is supported by evidence suggesting spores can be viable in seawater for up to a year (Shaw et al 2000b). Another, possibility is that the low overall genetic variation in L. salmonae could be the result of recent translocation of this parasite.…”
Section: Brown Et Al: Genetic Variation In Loma Salmonaesupporting
confidence: 56%
“…showed that spores of Loma salmonae could survive at 150 ppm iodine for 25 min, a dose typically used for disinfecting salmon eggs. The efficacy of chlorine and other disinfectants to kill microsporidia have been evaluated using direct exposure to animals , Khalifa et al 2001, Johnson et al 2003, infectivity of cell cultures (Wolk et al 2000and papers cited therein, Santillana-Hayat et al 2002, John et al 2003, Leiro et al 2004, Jordan 2005, Li & Fayer 2006, viability of spores detected by polar tube extrusion (He et al 1996, Keohane & Weiss 1999 and papers cited therein, Shaw et al 2001), or with stains that demonstrate either live or dead spores (Green et al 2000, Hoffman et al 2003. Green et al (2000) developed a method for evaluating viability of Encephalitozoon cuniculi using SYTOX Green in conjunction with Calcofluor White M2R™.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has also been shown that temperature regulates the rate of clearance of xenomas (Becker and Speare 2004b), which provides an interesting avenue through which to explore non-pharmacological methods of treatment. Shaw et al (2000b) investigated the viability of L. salmonae spores under laboratory conditions by polar filament extrusion and infectivity to Chinook salmon. Extrusion rates of isolated spores decreased from about 50% to zero by 100 d after storage in freshwater or seawater at 4°C.…”
Section: Temperature Effectsmentioning
confidence: 99%
“…References to details of experimental methods are cited below. In general, the sequelae of infection are similar with both hosts, except that Chinook are more susceptible (Shaw et al 2000b, Ramsay et al 2002 and they remain infected longer .…”
mentioning
confidence: 93%
See 1 more Smart Citation